Psychological Capital and Flourishing as Predictors of Work Engagement Among Private Secondary School Teachers in Alimosho L.G.A, Lagos State, Nigeria - Abiodun Adekunle Ogunola; Paul Akinkunmi Morakinyo (Journal of Social Studies, 2025)
The study investigated Psychological Capital and Flourishing as Predictor of Work Engagement among Private Secondary School Teachers in Alimosho Local Government Area of Lagos State, Nigeria. Teaching is a very unique field which remains a means of building knowledge and skills in students for the purpose of functionality in the society. This study examined psychological capital and  flourishing as predicting factors when it comes to coping with work, as it is believed that human resources and psychological strengths assist with improving an employee's work engagement. Research data for this present study was collected through the Psychological Capital Questionnaire (PCQ), Flourishing Scale (FS) and the Work Engagement Questionnaire (UWES-17). A sample of 224 teachers was selected for the study. The data was then analyzed using Statistical Package for the Social Sciences (SPSS). Independent T-Test and Multiple Regression Analysis are the test statistics employed. The study found that psychological capital and flourishing does influence work engagement amongst private secondary school teachers (R= .682a; F= 95.885; P < .000). The study concluded that high level of work engagement among teachers lead to many positive outcomes for an individuals, including increased productivity, job satisfaction, and retention.